Ranma 1/2. 4 - Takahashi, Rumiko, 1957- (Viz Media, 2014)
One day, teenage martial artist Ranma Saotome went on a training mission with his father and ended up taking a dive into some cursed springs at a legendary training ground in China. Now, every time he<U+2019>s splashed with cold water, he changes into a girl. His father, Genma, changes into a panda! What<U+2019>s a half-guy, half-girl to do? Contains volumes 7 and 8! Back when Ranma<U+2019>s father, Genma, and Akane<U+2019>s father, Soun, were young martial artists, they learned the secrets of Anything-Goes Martial Arts from one of the greatest masters of all time. Unfortunately, he<U+2019>s also someone they would do just about anything to get away from, and the entire Tendo household is about to find out why. Followed by a stirring rendition of Romeo and Juliet<U+2026>and Juliet<U+2026>and Romeo<U+2026>